Insights on the effect of ethanol on the formation of aromatics. (15th March 2020) - Wang, Qi; Saldinger, Jacob C.; Elvati, Paolo; Violi, Angela
Graphical abstract: Highlights: A newly merged gas-phase kinetic mechanism involving ethanol oxidation is validated. The effects of increasing ethanol content on gas-phase and PACs are discussed. The percentage of oxygenated PACs is not markedly affected by ethanol doping level. Most of oxygenated PACs are phenols, with 15% furans, and a small amount of ethers. Relative importance of oxygen and pure hydrocarbon growth mechanisms is highlighted. Abstract: For decades, ethanol has played an important role as a biofuel, as its addition to hydrocarbon fuels has been associated with a reduction in soot formation. The chemical mechanisms behind this phenomenon, however, are still not clear. In this paper, we contribute to this research area by elucidating the mechanisms that participate in the formation of polycyclic aromatic compounds (PACs) in an ethanol-doped ethylene flame, using a combination of deterministic and stochastic computational techniques. We specifically focus on the formation of oxygenated PACs and the chemical interactions of pure hydrocarbons and oxygen in six ethylene/air premixed flames with similar temperature profiles but different equivalence ratios and ethanol doping percentages. Our simulations confirm that an increase in the ethanol content results in a reduction of the formation of acetylene, small aromatics, and large PAHs. At the same time, the number of oxygenated PACs reach a maximum at a height above burner around 2–3 mm where they constitute 45% of all PACs: most of the oxygenated structures are phenols, mixed with approximately 15% of furans, and a small amount of ethers. Overall, the results indicate that the formation pathways of oxygenated PACs can compete with pure hydrocarbon growth mechanisms in the rapid growth region up to a height above burner of 2–3 mm. The rate of PACs' growth then gradually slows down, with pure hydrocarbon growth mechanisms being the main contributors in this region of the flame.